Pendampingan Kegiatan Berliterasi Bagi Siswa Tingkat Sekolah Dasar - Abdul Mukhlis; Hesti Feni Lia; Melly Khilda Khusana; Muhammad Rikzan Maulana (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
This activity aims to illustrate the implementation of the literacy festival model applied at Sendang Wonotunggal Public Elementary School. This activity is important to implement considering that preliminary studies indicate that student interest in literacy activities is relatively low. This is evident from the results of initial interviews, where 32% of students showed active reading, while only 28% completed writing assignments consistently. To address this issue, the mentoring team presented the idea of a community-based Literacy Festival that utilizes an action research cycle approach with three main stages: preparation, implementation, and evaluation. The collected data was analyzed interactively using the Mills and Huberman approach, with a systematic process of data reduction, data presentation, and conclusion drawing. The results showed that the literacy festival model was implemented through four series of activities: storytelling practice, creative writing practice, literacy quizzes, and language games, provided to second-, fourth-, and sixth-grade students at Sendang State Elementary School. These mentoring activities significantly assisted teachers and students in exploring and understanding literacy practices that foster language skills in students.